2019: Journals International Conference on Health Science, Green Economics, Educational Review and Technology (FULL CONTENT) - admin, admin (Universitas Efarina, 2019)
Papers in this edition were written by authors from 2 foreign countries and several lecturers and researchers from various universities in Indonesia.